Temporal Trajectories: A Comparative Analysis of Mexican and Vietnamese Students’ Strategies in the Canadian Edugration System - Cervantes-Macías, María; Delaisse, Anne-Cécile (Comparative and International Education / Éducation comparée et internationale, 2024)
This paper compares Mexican and Vietnamese international students’ and graduates’ migration decision-making while navigating Canadian policies merging international higher education and migration or the “edugration system.” While this system offers a delimited temporal framework and a linear pathway to permanent residency (PR) for international students; we argue that it does not align with the temporality of international students’ and graduates’ plans and aspirations. We draw from interviews conducted with 15 Mexican students and six graduates as well as 10 Vietnamese students and 11 graduates. Our findings highlight participants’ migration strategies for transnational social mobility, from childhood to postgraduation. These strategies unfold distinctively in time, depending on the region of origin. Rather than embracing the homogenizing edugration time frame, there is a need to emphasize international students’ and graduates’ own temporality to foster a nuanced and critical understanding of their migration pathways.